Exploring Herbicidal Potential of Aqueous Extracts of Some Herbaceous Plants Against Parthenium Weed - SAFDAR,M.E. (2016)
To assess the phytotoxic potential of Achyranthes aspera, Alternanthera philoxeroides, Datura metel and Rumex dentatus against Parthenium hysterophorus, 5% (w/v on dry weight basis) aqueous extracts from root, stem, leaf, flower and whole plant were tested through a Petri plate-based germination and pot-cultured seedling bioassays. Achyranthes aspera and A. philoxeroides inhibited parthenium weed germination more than extracts from other species. Whole plant, leaf and fruit extracts of A. aspera reduced the germination percentage (5%); leaf extract from A. philoxeroides caused lower germination index (0.4), higher mean germination time (14 d) and longer time to 50% germination (13.5 d) of parthenium weed. In the foliar spray bioassay, A. aspera reduced parthenium weed shoot growth more than the other species whereas R. dentatus caused more reduction in root growth. Whole plant extract from A. aspera caused maximum reduction in parthenium weed seedling vigor index (98%) and seedling biomass (96%). The aqueous extracts of A. aspera and A. philoxeroides contained higher concentrations of phenolics viz. gallic (16.9 mg L-1), caffeic (7.4 mg L-1), chromatotropic (63.8 mg L-1), p-coumaric (10.5 mg L-1), m-coumaric (3.1 mg L-1), syringic (9.21 mg L-1) and 4 hydroxy-3-methoxy benzoic (118.6 mg L-1) acids compared with extracts of the other two species tested.